CLUSTERED BASED TECHNOLOGICAL AND ORGANIZATIONAL ASPECTS OF MOBILE DEVICE MANAGEMENT AND THEIR SECURITY CONCERNS - Dr. L. K Suresh Kumar (The Bioscan, 2024)
Due to security concerns, mobile device management (MDM) is gaining importance in enterprises. Unlike permanent equipment, which may be controlled by companies and local administrations, mobile devices can move about. Android powers the vast majority of modern smartphones. Here we will go over some of the current MDM-solutions, how they work, and how they affect change management. The purpose of this study is not to argue for or against any particular MDM-system. Mobile device management segmentation in cloud-based and on-premises operations, as well as the bring-your-own-device policy in comparison to company-owned devices, are discussed in the paper. The article delves into the features, aspects, security issues, and application of mobile device management. Additionally, we cover the present state of the industry's market, the mobile device management landscape, the significance and benefits of this field, and more.